Transdermal microneedle-assisted ultrasound-enhanced CRISPRa system to enable sono-gene therapy for obesity - Shaoyue Li; Jifeng Yu; Yuting Shen; Bing Xiong; De Zhao; Weichen Xu; Shen Zhang; Xin Guan; Yunyun Liu; Xuexia Shan; Anqi Zhu; Qi Lyu; et al. (Nature Communications)
Abstract Obesity, a surging global health challenge, necessitates effective, accessible and innovative therapeutic models. Here we develop a spatiotemporally controllable microneedle (MN) drug delivery platform for sono-gene therapy to fight obesity. The platform delivers the methoxy polyethylene glycol-polyethyleneimine (mPEG-PEI) modified metal-organic frameworks (MOFs) sonosensitizer and the clustered regularly interspaced short palindromic repeats-activating (CRISPRa)/CRISPRa-uncoupling protein 1 (UCP1) system intradermally to adipocytes. Overall, this therapy platform is capable of achieving two major strategies of “annihilation” and “countermeasure”: one is to kill redundant white adipocytes by sonodynamic therapy, and the other is to promote the browning of white adipocytes through the controllable release of CRISPRa-UCP1 system and sonodynamic effect. Obese male mice treated with this sono-gene therapy shows significant ameliorate in glucose tolerance and insulin sensitivity, successfully achieves weight loss and restrains weight rebound. This study may enable a standard treatment paradigm for sono-gene therapy of obesity and other metabolic diseases.